in Differential Equations recategorized by
120 views
0 votes
0 votes

The general solution of $\dfrac{\mathrm{d^{2}} y}{\mathrm{d} x^{2}}-6\dfrac{\mathrm{d} y}{\mathrm{d} x}+9y=0$ is

  1. $y=C_{1}e^{3x}+C_{2}e^{-3x}$
  2. $y=(C_{1}+C_{2}x)e^{-3x}$
  3. $y=(C_{1}+C_{2}x)e^{3x}$
  4. $y=C_{1}e^{3x}$
in Differential Equations recategorized by
1.9k points
120 views

Please log in or register to answer this question.

Welcome to GO Electronics, where you can ask questions and receive answers from other members of the community.